Linguocultural Analysis Of Game Names In The English Language - Mengboyev Azizbek Alijon ugli (Peerian Journals Publishing, 2024)
This article explores the linguocultural features of game names in the English language, offering insight into how cultural values, societal trends, and linguistic creativity shape their formation. Game names are not merely functional labels but serve as a reflection of the cultural identity, history, and values of English-speaking societies. By analyzing names across three major categories—video games, board games, and traditional games—this study uncovers how linguistic devices such as compounding, metaphor, symbolism, and alliteration contribute to their memorability and cultural resonance. Additionally, the research highlights the ways game names represent cultural ideals, such as heroism, competition, technological progress, and entertainment, while simultaneously adapting to global trends. This interdisciplinary exploration provides a deeper understanding of the dynamic interplay between language, culture, and the ever-evolving gaming industry
Keywords: Linguoculture; game names; encapsulate layers